The Role of Family in the Prevention of Violence During Sports Manifestation (Annual of the Faculty of Philosophy in Skopje, 2017)
In the globalization era, the era of technological development and advancement, in the era of expansion of information and the information boom, certain segments of society and phenomena, not only did not join their progressive discourse, by contrast, they suffered recourse and on behalf of them, others that can be freely included in the category of social deviations, did not lose breath with the modern times and have been established on the surface of the society. The family, as a significant factor, suffered a series of transformations in recent decades, but it can still be considered as an institution that is the first bastion in preventing violence. Violent behaviour, especially in recent decades, is increasing. Therefore, one of the key issues that arises in scientific elite’s discussions is how it can be prevented properly and truly. Among all types of violence that are part of our everyday lives, violence at sports events predominates. Studies show that the family as an institution, is an important factor in the prevention of violence at sports events.
Keywords: FAMILY; VIOLENCE; VIOLENT BEHAVIOUR; SPORTS MANIFESTATIONS